Drainage Behavior of Sports Pitches–A Case Study Review. Issue 1 (19th October 2017) - Fleming, P.R.; Frost, M.W.; Simpson, M.; Everett, R.; Gibbs, R.J.
Abstract : The drainage behavior of sports pitches has traditionally been designed from experience with hydraulic performance rarely measured in detail. Within the wider industry and regulatory bodies there is a perception that storm water and increased drainage rates from sports pitches contribute to local flood risk. Empirical observations have suggested that in reality pitch drainage systems may discharge water at low volumes and rates and there is often limited surface run‐off. Furthermore it appears that lack of technical guidance on the discharge of water from sport pitch drainage systems may have led to misunderstanding their drainage behavior and possible benefits they could bring to water management as opposed to perceived dis‐benefits. This paper summarizes selected results of a case study which included field measurements of weather and discharge behavior on a range of natural turf sports pitches in England. The findings from this study indicate that natural turf sports pitches can provide resistance to flow and hence advantageous attenuation of rainfall and storm water. Additionally sports pitches can store large volumes of water within the pervious materials used in their design. The study has confirmed that sport pitches demonstrate the key functions that are reflected in the design requirements of Sustainable Urban Drainage Systems (SuDs) such as pervious pavements providing source control of surface rain water.